Ionic liquid electrolyte selection for high voltage supercapacitors in high-temperature applications - Bahaa, Ahmed; Alhammadi, Ayoob; Lethesh, Kallidanthiyil Chellappan; Susantyoko, Rahmat Agung; Bamgbopa, Musbaudeen O. (Frontiers in Chemistry, 2024)
Systematic analyses of electrolyte physicochemical properties are important to screen ionic liquids (ILs) and understand the electrochemical performance of supercapacitor electrolytes. This study harmonizes the evaluation of electrochemical performance and transport properties of eight shortlisted ILs from 22 commercially available hydrophobic ILs toward achieving a ≥ 5 V supercapacitor capable of high-temperature operation (up to 353.15 K). The eight ILs are N-Propyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ([Pyr 1, 3] [TFSI], N-Pentyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ([Pyr 1, 5] [TFSI]), N-Propyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide ([Pyr 1, 3] [FSI]), 1-Methyl-1-(2-methoxyethyl)pyrrolidinium Bis(trifluoromethanesulfonyl)imide ([Pyr 1, 102] [TFSI]), 1-Methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide ([Pip 1, 3] [TFSI]), 1-Methyl-1-propylpiperidinium bis(fluorosulfonyl)imide ([Pip 1, 3] [FSI]), N-Trimethyl-N-propylammonium bis(trifluoromethanesulfonyl)imide ([N 111, 3] [TFSI]), N-Trimethyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide ([N 111, 6] [TFSI]). The density, viscosity, and ionic conductivity of the eight ILs were measured between 278.15 and 373.15 K to confirm the effects of temperature and ion structure before electrochemical characterization. The [FSI]-based ILs ([Pip 1, 3] [FSI] and [Pyr 1, 3] [FSI]) showed lower densities and viscosities compared to other ILs among the eight based on [TFSI]. Consequently, the highest conductivity was obtained for [Pyr 1, 3] [FSI]. Cyclic voltammetry and impedance spectroscopy was performed on supercapacitors assembled with the eight ILs as electrolytes between 298.15–353.15 K. Conclusion from the two-electrode supercapacitors using multi-walled carbon nanotubes showed the 6 most-applicable ILs towards the targeted ≥ 5 V SC at high temperature are [Pip 1, 3] [TFSI] (5.4 V), [Pip 1, 3] [FSI] (5 V), [N 111, 3] [TFSI] (5.1 V), [N 111, 6] [TFSI] (5.2 V), [Pyr 1, 102] [TFSI] (5.2 V), and [Pyr 1, 5] [TFSI] (5.2 V).